"Power to the workers": Empowering shop floor workers with worker-centric digital designs. Issue 1 (7th January 2019) - Leyer, Michael; Richter, Alexander; Steinhüser, Melanie
Abstract : Purpose: The purpose of this paper is to reveal how information and communication technology (ICT) can empower shop floor workers in collaborative manufacturing environments. Design/methodology/approach: The authors gather data from a mobile maintenance department of a steel manufacturing company and apply the method of a scenario-based design. The authors use data from interviews, observations and company documents to create problem and activity scenarios. The authors also demonstrate the development of a worker-centric digital design in multiple demonstration and evaluation cycles. Findings: The authors find that ICT can be used to ensure that empowerment is not only a concept, but can sustainably empower daily operations. Research limitations/implications: The authors contribute to theory by showing how structural empowerment can be used as a guiding theoretical lens to design ICT for shop floor workers in collaborative manufacturing work environments. These implications are limited to findings from a single case study. Practical implications: The results provide an overview of different empowerment dimensions, namely, the access to information, resources, support and opportunities, that can support employees in collaborative manufacturing environments. Originality/value: This paper is first in suggesting a framework of how ICT designs can be used to empower shop floor workers in collaborative manufacturing environments.